A new NMR approach for structure determination of thermally unstable biflavanones and application to phytochemicals from Garcinia buchananii. (20th July 2015) - Stark, Timo D.; Lösch, Sofie; Salger, Mathias; Balemba, Onesmo B.; Wakamatsu, Junichiro; Frank, Oliver; Hofmann, Thomas
Abstract Previous activity‐guided phytochemical studies on Garcinia buchananii stem bark, which is traditionally used in Africa to treat various gastrointestinal and metabolic illnesses, revealed xanthones, polyisoprenylated benzophenones, flavanone‐C‐glycosides, biflavonoids, and/or biflavanones as bioactive key molecules. Unequivocal structure elucidation of biflavonoids and biflavanones by means of NMR spectroscopy is often complicated by the hindered rotation of the monomers around the C‐C axis (atropisomerism), resulting in a high spectral complexity. In order to facilitate an unrestricted rotation, NMR spectra are usually recorded at elevated temperatures, commonly over 80 °C, which effects in a single set of resonance signals. However, under these conditions, one of the target compounds of this investigation, (2R, 3S, 2″R, 3″R)‐manniflavanone (1), undergoes degradation. Therefore, we demonstrated in the present study that the 1, 1‐ADEQUATE could be successfully used as a powerful alternative approach to confirm the C‐C connectivities in 1, avoiding detrimental conditions. However, a moderate increase in temperature up to 50 °C was sufficient to deliver sharp signals in the proton NMR experiment of (2R, 3S, 2″R, 3″R)‐isomanniflavanone (2) and (2″R, 3″R)‐preussianone (3). In addition, two new compounds could be isolated, namely (2R, 3S, 2″R, 3″R)‐GB‐2 7″‐O‐β‐d‐glucopyranoside (4) and (2R, 3S, 2″R, 3″R)‐manniflavanone‐7″‐O‐β‐d‐glucopyranoside (5), and whose structures were elucidated by spectroscopic analysis including 1D and 2D NMR and mass spectrometry methods. The absolute configurations were determined by a combination of NMR and electronic circular dichroism (ECD) spectroscopy. The aforementioned compounds exhibited high anti‐oxidative capacity in the H2O2 scavenging, hydrophilic Trolox equivalent antioxidant capacity (H‐TEAC) and hydrophilic oxygen radical absorbance capacity (H‐ORAC) assays. Copyright © 2015 John Wiley & Sons, Ltd.